Free-fatty acid profile obtained by enzymatic solvent-free hydrolysis of sunflower and soybean lecithins - Penci, Maria Cecilia (2010)
The free-fatty acid profile of sunflower and soybean lecithins generated by enzymatic hydrolysis was determined by capillary gas chromatography using the internal standard method. This procedure involves the previous lipid extraction, clean-up and fatty-acid methyl-esters preparation. Different conventional methods commonly employed to calculate the hydrolysis degree in both substrates were compared. The fatty-acid profile of sunflower and soybean phospholipids and its initial acidity composition were chromatographically determined. Results from recovery studies were satisfactory (98% and 108% for soybean and sunflower, respectively). The effect of temperature (50 and 60 °C) and pH conditions (pH 7 and pH 8) on lecithin-hydrolysis degree was evaluated, being temperature the most affecting parameter. The profile of the fatty acids liberated after hydrolysis depended on both the enzyme and the pH of reaction mixture. Finally, the chromatographic methodology employed in this paper may be useful to study the lecithin enzymatic modification in order to produce emulsifiers with specific characteristics.